Education and Socialization for Elderly: A Comparative Study between Portugal and Italy - Rute Cristóvão Ricardo; Andrea Porcarelli (Adult Education Research Conference, 2019)
Universities of Third Age (UTA) have been assuming a central role in elderly education. This research investigates the dynamics of education and socialization in UTA, considering impacts on individuals.
Keywords: Education; Socialization; Elderly; Universities of Third Age